What's in a Scriven Number? - Abhik R. Roy; Kristin A. Hobson; Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2012)
Background: Other than Leonhard Euler, one of the greatest physicists and mathematicians ever to have lived and dubbed "...c'est notre maître à tous" or "...the master of us all" by the French mathematician and astronomer Pierre-Simon Laplace, Paul Erdös was a mathematician who published more papers in mathematics than anyone else (Hoffman, 1998). Because of this feat, friends and colleagues created what has been known as an Erdös number. An Erdös number describes a person's degree of separation from Erdös through collaborations directly with him or with others who have collaborated with him.   Purpose: In this paper, we present reasoning similar to that of an Erdös number for Michael Scriven who is widely considered to be one of the leading theorists in evaluation. With his numerous publications and influence on the theory and practice of evaluation, we present not only the hope, but also the need for a Scriven number. Setting: Not applicable.   Intervention: Scriven number.   Research Design: Not applicable.   Data Collection and Analysis: Not applicable.   Findings: A collaborative count such as a Scriven number would centralize evaluation. A Scriven number would form new connections and collaborations, thus yielding a robust connectivity. Keywords: Scriven number